2011
DOI: 10.1038/nmeth.1583
|View full text |Cite
|
Sign up to set email alerts
|

Two-color nanoscopy of three-dimensional volumes by 4Pi detection of stochastically switched fluorophores

Abstract: We demonstrate three-dimensional (3D) super-resolution imaging of stochastically switched fluorophores distributed across whole cells. By evaluating the higher moments of the diffraction spot provided by a 4Pi detection scheme, single markers can be simultaneously localized with <10 nm precision in three dimensions in a layer of 650 nm thickness at an arbitrarily selected depth in the sample. By splitting the fluorescence light into orthogonal polarization states, our 4Pi setup also facilitates the 3D nanoscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
234
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 220 publications
(239 citation statements)
references
References 34 publications
3
234
0
2
Order By: Relevance
“…S7). The z coordinates of the molecules can be obtained by a variety of means for 3D super-resolution imaging (21)(22)(23)(24)(25)(26), and indeed 3D STORM has been demonstrated in live cells (31). However, the use of diffusing membrane probes presents an additional challenge, especially when the shapes of the single-molecule images are used to determine their z-positions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…S7). The z coordinates of the molecules can be obtained by a variety of means for 3D super-resolution imaging (21)(22)(23)(24)(25)(26), and indeed 3D STORM has been demonstrated in live cells (31). However, the use of diffusing membrane probes presents an additional challenge, especially when the shapes of the single-molecule images are used to determine their z-positions.…”
Section: Discussionmentioning
confidence: 99%
“…It has been further demonstrated that many conventional dyes can be used for super-resolution imaging based on photoswitching/bleaching and localization of single molecules (11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Using single-molecule-based super-resolution methods, 3D resolutions down to approximately 10 nm have been demonstrated for fixed samples (21)(22)(23)(24)(25)(26), and live-cell imaging has also been achieved with spatial resolutions of 20-60 nm at time resolutions ranging from 0.5 s to 1 min (27)(28)(29)(30)(31)(32).…”
mentioning
confidence: 99%
“…These methods can achieve precisions below 100 nm in 3D over a 2-μm range (14,19,20). In addition, sub-10-nm precision can be obtained via interferometry (21); however, these methods severely restrict the sample geometry, have a shallower operational depth of field (∼650 nm) (22), and are not yet conducive to live-cell imaging.…”
mentioning
confidence: 99%
“…It is worth noting that localisation precision is not equivalent to resolution: The resolution achieved with LM strategies depends very much on the available photons, but also on the labelling density and the experimental configurations. For biological samples, it is generally around 20 nm in the lateral dimension (up to ≈4 nm [32]) and around 70 nm in the axial dimension (up to ≈6 nm [33]). …”
Section: Localisation Microscopymentioning
confidence: 99%
“…Superb lateral and axial resolution (≈4 and 5.4 nm, respectively [32,33]) has been achieved sandwiching the sample between two objectives to exploit the self-interference of emitted photons while taking advantage of the extra budget of photons available for improved localisation in all directions (interferometric PALM, iPALM or 4Pi-LM) [32,33,61]. This approach is limited to a 1-μm-thick optical layer (although the sample can be thicker) and is constrained by the severe complexity of the experimental setup.…”
Section: Stochastic Localisation Microscopy In 3dmentioning
confidence: 99%